China in Ethiopia : The Long-Term Perspective - Tesfaye, Aaron (Book collections on Project MUSE., 2020)
"This comprehensive study of China-Ethiopia relations examines why China-an economic and emerging global power-has built relations with Ethiopia and why Ethiopia has responded by singling out China as a partner in its quest for economic development. Using middle-range theory and field research, Aaron Tesfaye focuses on three sets of phenomena: political, economic, and strategic. He explores the following questions: Why are China and Ethiopia building relations at this juncture of globalization? What motivates China's role in helping build Ethiopia's infrastructure, and is Ethiopia's debt to China sustainable? What can Ethiopia offer China in terms of strategic interest in the Horn of Africa and the Red Sea littoral, which is now the most sought out area for military bases by regional and international forces? Tesfaye argues that China's ability to meet Africa's tremendous demand for capital and technology is a reflection of its economic and military rise and evidence that the Asian Century has arrived, ushering in a new global reality"--